2020
DOI: 10.3389/fimmu.2020.01958
|View full text |Cite
|
Sign up to set email alerts
|

Specific Targeting of Notch Ligand-Receptor Interactions to Modulate Immune Responses: A Review of Clinical and Preclinical Findings

Abstract: Understanding and targeting Notch signaling effectively has long been valued in the field of cancer and other immune disorders. Here, we discuss key discoveries at the intersection of Notch signaling, cancer and immunology. While there is a plethora of Notch targeting agents tested in vitro, in vivo and in clinic, undesirable off-target effects and therapy-related toxicities have been significant obstacles. We make a case for the clinical application of ligand-derived and affinity modifying compounds as novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 150 publications
0
15
0
Order By: Relevance
“…Subsequent survival analysis indicated that the high-risk group was associated with poorer prognosis, which was verified by an independent GEO cohort. GSEA analysis showed that the high-risk group was significantly enriched in pathways for tumor progression, such as the JAK-STAT signaling pathway (36), cancer in pathway, TGF-b signaling pathway (37,38), and NOTCH signaling pathway (39), leading to poor prognosis. In the hypoxic microenvironment, HIFs are the main regulators of hypoxic response (18,35).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent survival analysis indicated that the high-risk group was associated with poorer prognosis, which was verified by an independent GEO cohort. GSEA analysis showed that the high-risk group was significantly enriched in pathways for tumor progression, such as the JAK-STAT signaling pathway (36), cancer in pathway, TGF-b signaling pathway (37,38), and NOTCH signaling pathway (39), leading to poor prognosis. In the hypoxic microenvironment, HIFs are the main regulators of hypoxic response (18,35).…”
Section: Discussionmentioning
confidence: 99%
“…The alleviation of tumor tissue hypoxia is therefore a promising way to overcome the immunosuppressive TME and to enhance cancer immunotherapy 4 , 5 . Targeting of proangiogenic factors, such as vascular endothelial growth factor (VEGF) signaling, can normalize tumor blood vessels, reduce hypoxia, and increase tumor-infiltrating CD8 + T cells while reducing Tregs and MDSCs, resulting in better therapeutic efficacies 4 , 6 . However, the vascular normalization window with current available anti-angiogenic therapies is transient, which limits its benefit for cancer immunotherapy.…”
mentioning
confidence: 99%
“…Given the involvement of Notch in both development and disease, targeting Notch for a plethora of therapeutic purposes has been researched extensively [38]. These efforts have yielded multiple active molecules such as small-molecule drugs (e.g., γ-secretase inhibitors), antibodies, peptides, and microRNAs that target ligand-receptor interactions, receptor processing, or the expression of Notch pathway components [38,39,[82][83][84]. Most were developed as inhibitors of the pathway, although some could be used as activators.…”
Section: Box 2 Small Drugs and Other Molecules For Notch Modulationmentioning
confidence: 99%